Genetic characterization and antimicrobial susceptibility of Escherichia coli isolated from household water sources in northern Ghana. (19th April 2022) - Kichana, Elvis; Addy, Francis; Dufailu, Osman Adamu
Abstract: The microbial quality of household water is an important issue in developing countries, especially in Ghana, where many people still depend on unimproved sources of water. The present study investigated the prevalence, genetic characteristics, and antimicrobial resistance profile of Escherichia coli from surface water sources. Fifty-two water samples were analyzed by using a spread plate, a biochemical test, and multiplex polymerase chain reactions . E. coli was isolated from each of the 52 water samples. Of these isolates, 75% were noted to possess virulence genes. Approximately 54% of the isolates were characterized as follows: enterotoxigenic E. coli (ETEC, 10.26%), enteropathogenic E. coli (EPEC, 17.95%), verotoxigenic E. coli (VTEC, 23.07%), and enteroinvasive E. coli (EIEC, 2.57%). Eighteen of the fifty-two isolates could not be characterized due to heterogeneity in banding. The disc diffusion method was used to test for antimicrobial susceptibility. The isolates were most resistant to ceftazidime, augmentin, and cefuroxime. Multidrug resistance was recorded in 48.1% of the isolates. In contrast, the isolates were most susceptible to ciprofloxacin (86.5%), nitrofurantoin (84.6%), and ofloxacin (75%). These results revealed a high diversity and widespread of E. coli in northern Ghana. The study provides important data for public health nationwide surveillance of E. coli in surface water across the country. HIGHLIGHTS: This study explains the high occurrence of pathogenic E. coli in drinking water sources. There is a high occurrence of uncharacterized E. coli isolates with ambiguous banding patterns. A high record of multidrug resistance E. coli is explained. A reduction in the efficacy of important antimicrobials is found. Graphical Abstract